GE_GERICHTE A/1306/2008 vom 28. Januar 2009 - GE Cour de justice (2009)
; LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE ; OPPOSITION(PROCÉDURE) ; AVOCAT ; MANDATAIRE ; DÉPENS ; COMPLEXITÉ DE LA PROCÉDURE | LPGA52